The morphological structure of the synovial membrane in rheumatoid arthritis. - Komarova, E. B.; Kurinnyi, A. B. (Морфологія / Morphologia / Morfologìâ, 2013)
Background. Rheumatoid arthritis - an autoimmune disease which is characterized by inflammatory and proliferative processes in the synovium; a few studies have shown that there are significant differences in the structure of synovium at different stages of rheumatoid arthritis, but further investigation is needed to detail this data. Objective. To study the morphology of the synovial membrane, depending on the duration of rheumatoid arthritis. Methods. Patients were divided into 2 groups: the first included 10 patients with rheumatoid arthritis lasting up to 2 years (12,85±7,61 months), 2nd group consisted of 11 patients with RA duration from 2 to 8 years (5,8±1,8 years). Verification of the diagnosis was performed according to the АСR/EULAR, 2010 criteria. Patients underwent arthroscopic examination with biopsy and subsequent histological analysis. Results. In patients of the 1st group the signs of angiogenesis, focal lymphoid infiltration and edema of the synovial membrane were most frequently seen, that may indicate a predominance of immune inflammatory processes and neo-angiogenesis at early stages of pathogenesis. In patients of the 2nd group the signs of severe synoviocyte proliferation (more than 6 layers), hyperplasia of villous, diffuse lymphoid infiltration, and mucoid swelling were seen more often. It confirms the data about the prevalence of proliferation and connective tissue disorganization at later stages of the pathogenesis of rheumatoid arthritis. Conclusion. The data obtained let us develop a differentiated approach to the complex treatment of rheumatoid arthritis with varied duration of the disease.